Analisis Multimodal pada Teks Iklan untuk Mengidentifikasi Aspek Ketulusan Iklan - Lee Seung Hoon; Syihabuddin Syihabuddin; Dadang Sudana; Wawan Gunawan (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2023)
This study aims to analyze the sincerity aspect of Indonesian and Korean advertisements through multimodal analysis. This study uses a content analysis research method using the FCB Grid Model on several products, namely fast food, tobacco, and telecommunications. The selection of ad samples was carried out based on the FCB Grid Model. The results of the study show that some products such as tobacco and fast food are included in the category of products that involve low emotions and thoughts when consumers consider these products. However, telecommunications products fall into the category of products that involve high rational thinking skills, thus requiring serious consideration from consumers. Other findings show that there are several semantic and pragmatic expressions that make consumers confused in choosing a product. The most frequent violations found in products are false expressions and explanations that lead consumers astray. In addition, other violations are expression omissions, exaggerated expressions, fictitious, and omission of important information, thus making consumers feel lost in choosing products.